2015
DOI: 10.1002/ece3.1485
|View full text |Cite
|
Sign up to set email alerts
|

Divergence thresholds and divergent biodiversity estimates: can metabarcoding reliably describe zooplankton communities?

Abstract: DNA metabarcoding is a promising method for describing communities and estimating biodiversity. This approach uses high-throughput sequencing of targeted markers to identify species in a complex sample. By convention, sequences are clustered at a predefined sequence divergence threshold (often 3%) into operational taxonomic units (OTUs) that serve as a proxy for species. However, variable levels of interspecific marker variation across taxonomic groups make clustering sequences from a phylogenetically diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
136
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(139 citation statements)
references
References 64 publications
(144 reference statements)
3
136
0
Order By: Relevance
“…Only two studies (Dowle et al, 2015;Elbrecht and Leese, 2015) have performed a robust benchmarking of metabarcoding using freshwater invertebrates and showed that this technique can be successfully applied to biodiversity assessment. In marine metazoans, all studies have focused only on plankton samples (Brown et al, 2015;Mohrbeck et al, 2015;Albaina et al, 2016). Thus, an exhaustive evaluation of metabarcoding for marine benthic metazoan taxonomic inferences is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Only two studies (Dowle et al, 2015;Elbrecht and Leese, 2015) have performed a robust benchmarking of metabarcoding using freshwater invertebrates and showed that this technique can be successfully applied to biodiversity assessment. In marine metazoans, all studies have focused only on plankton samples (Brown et al, 2015;Mohrbeck et al, 2015;Albaina et al, 2016). Thus, an exhaustive evaluation of metabarcoding for marine benthic metazoan taxonomic inferences is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, these high numbers may be due to missing intraspecific sequence variation in the PR 2 reference database, which usually contains only one accession per species. In natural communities, intraspecific genetic variation of microbial organisms may be much more diverse than just a few base pair differences, especially in hypervariable gene regions (Brown et al, 2015;Decelle et al, 2014;Dunthorn et al, 2012;Pernice et al, 2013 (2014) and Gimmler and Stoeck (2015).…”
Section: Contrasting Otu Results From Three Approachesmentioning
confidence: 99%
“…These clean reads were then clustered into Operational Taxonomic Units (OTUs) using UPARSE with a 97% similarity threshold, resulting in a total of 4,598 OTUs for V4 and 4,176 OTUs for V8-9 region. Even though there is no clear consensus on the optimal threshold to use in clustering algorithms Brown et al, 2015), we decided to use 97% because it has been widely used (Stoeck et al, 2010;Kammerlander et al, 2015;Massana et al, 2015;Giner et al, 2016;Kim et al, 2016). We are aware that this threshold might group species or even genus into the same OTU.…”
Section: Clustering and Taxonomical Annotationmentioning
confidence: 99%